Dependence or Independence? ——The Attempting Discussion on “Three-Self” of Hong Kong Pentecostal Mission - CHEN, Mingli (Journal of Research for Christianity in China (JRCC), 2023)
In the first half of the twentieth century, the independent of Chinese Churches became an irresistible trend, but the achievements were not satisfying. At that time, one new sect of Christianity—the Pentecost came into China. Meanwhile, the Pentecostal groups became independent gradually, there were some churches established by the Chinese only. In the early history of Hong Kong Pentecostal Mission, on the one hand, the independent Pentecostal missionaries didn’t have strong financial support, and because of the limit of native language and pursuing the breadth of ministry, they gave the Chinese believers enough space and authority to independence; on the other hand, the native evangelists grew up gradually at the same time, they raised money actively, undertook the different responsibilities of this community. On the whole, the Hong Kong Pentecostal Mission realized the “three-self principle”.
Keywords: The Pentecost, Independence, Hong Kong Pentecostal Mission